2014
DOI: 10.1007/s00276-014-1391-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary acquired nasolacrimal duct obstruction: is it really related to paranasal abnormalities?

Abstract: The incidence of PANDO may not be directly related to paranasal abnormalities. Further large-scale studies should be performed to clarify the relationship between paranasal abnormalities and PANDO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…Reduced lacrimal flow was found in 45.8% ( n = 24) cases which resolved after surgical correction of nasal septum. Radiological anatomy of nose and NLD assessment by Yazici et al 11 showed increased incidence of deviated nasal septum toward the side of PANDO ( P = 0.008). However, no differences were noted for other paranasal abnormalities between PANDO and the control groups.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Reduced lacrimal flow was found in 45.8% ( n = 24) cases which resolved after surgical correction of nasal septum. Radiological anatomy of nose and NLD assessment by Yazici et al 11 showed increased incidence of deviated nasal septum toward the side of PANDO ( P = 0.008). However, no differences were noted for other paranasal abnormalities between PANDO and the control groups.…”
Section: Discussionmentioning
confidence: 97%
“…Apart from nasal septum, no other intranasal features were documented in these studies. Computed tomography based data exists on associated sino-nasal anomalies in PANDO 6, 7, 8, 9, 10, 11, 12. Similar significant endoscopic intranasal anomalies and pathologies have been described to be associated with congenital nasolacrimal duct obstruction 13 .…”
Section: Introductionmentioning
confidence: 88%
“…However, in addition the authors found that only the side of the septal deviation was correlated with the side of the acquired NLDO (p = 0.008). 9 Dikici et al examined the relationship between NSD and paranasal abnormalities in the etiology of primary acquired NLDO. The authors established a statistically signi cant relationship between acquired NLDO and the axial location of NSD classi cation, axial angle of septal deviation classi cation, paradoxical middle turbinate, angle between the bony inferior turbinate and medial wall of the maxillary sinus and inferior meatus measure.…”
Section: Discussionmentioning
confidence: 99%
“…7 There are other studies that examined nasal pathologies and nasolacrimal duct obstruction in adult patients. [8][9][10][11] In the literature, there is only one study in which nasal endoscopic examinations were assessed in patients requiring surgical intervention due to CNLDO. The said study examined 100 pediatric patients undergoing surgery for epiphora (probing and syringing of the nasolacrimal ducts) and in each case detected nasal septal deviation.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Nasolacrimal duct obstruction may have different etiologies and can be either primary or secondary, with primary acquired nasolacrimal duct obstruction (PANDO) being the most common. 2 , 3 , 4 , 5 The secondary causes, which can ultimately affect all sections of the draining lacrimal duct, include infectious, inflammatory, neoplastic, traumatic and mechanical blockage and are summarized under the term “secondary acquired nasolacrimal drainage obstruction” (SANDO). 6 , 7 At Humanitas Research Hospital, Eye center, the diagnosis lies essentially in the ophthalmological examination, including the lacrimal duct probing with the Bowman probe and, if necessary, lacrimal duct flushing.…”
Section: Introductionmentioning
confidence: 99%